2000
DOI: 10.1128/aem.66.11.4688-4695.2000
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of pRGO1, a Plasmid from Propionibacterium acidipropionici , and Its Use for Development of a Host-Vector System in Propionibacteria

Abstract: The complete nucleotide sequence of pRGO1, a cryptic plasmid from Propionibacterium acidipropionici E214, was determined. pRGO1 is 6,868 bp long, and its G؉C content is 65.0%. Frame analysis of the sequence revealed six open reading frames, which were designated Orf1 to Orf6. The deduced amino acid sequences of Orf1 and Orf2 showed extensive similarities to an initiator of plasmid replication, the Rep protein, of various plasmids of gram-positive bacteria. The amino acid sequence of the putative translation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 38 publications
1
52
0
Order By: Relevance
“…The nucleotide sequence of pLME106 from P. jensenii DF1 was determined by Stierli [26,42]. This sequence is 100% identical to the nucleotide sequence of plasmid pRGO1 from P. acidipropionici E214 [36], determined by Kiatpapan et al [17,18]. The size of plasmid pLME106/pRGO1 is 6868 bp, the G+C content is 65%.…”
Section: Determination Of the Nucleotide Sequences Of Propionibacterimentioning
confidence: 99%
See 4 more Smart Citations
“…The nucleotide sequence of pLME106 from P. jensenii DF1 was determined by Stierli [26,42]. This sequence is 100% identical to the nucleotide sequence of plasmid pRGO1 from P. acidipropionici E214 [36], determined by Kiatpapan et al [17,18]. The size of plasmid pLME106/pRGO1 is 6868 bp, the G+C content is 65%.…”
Section: Determination Of the Nucleotide Sequences Of Propionibacterimentioning
confidence: 99%
“…It was suggested that pLME106/pRGO1 is a composite plasmid, which must have gained ppnA and orf5 from another organism [29]. ORF3, encoding a putative protein of unknown function, was not described by Kiatpapan et al [17,18] either.…”
Section: Plme106 From P Jensenii Df1 and Prgo1 From P Acidipropionimentioning
confidence: 99%
See 3 more Smart Citations